2020
DOI: 10.26686/wgtn.12552197.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A vocabulary size test

Abstract: No description supplied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 0 publications
1
152
0
2
Order By: Relevance
“…Object Relative The girl was the one that the man fed. Nation and Beglar (2007;see also Beglar, 2009). The original test systematically samples 14 frequency levels established using data from the spoken part of the BNC.…”
Section: Subject Relativementioning
confidence: 92%
“…Object Relative The girl was the one that the man fed. Nation and Beglar (2007;see also Beglar, 2009). The original test systematically samples 14 frequency levels established using data from the spoken part of the BNC.…”
Section: Subject Relativementioning
confidence: 92%
“…According to an in‐house English language proficiency test using CEFR as the underlying test construct, the students’ English proficiency at the time of the experiment was equivalent to CEFR B2+ or to IELTS overall band score of 5.5 (i.e., upper intermediate). In addition to the aforementioned proficiency test, we administered Nation and Beglar's () Vocabulary Size Test (VST), which indicated that these learners had receptive knowledge of at least the 4,000 most frequent word families in English. As all the data in these tests were normally distributed, and t ‐tests for independent samples were run to compare the two groups’ L2 proficiency test scores and their VST scores.…”
Section: Methodsmentioning
confidence: 99%
“…The selection was based on the requirement that at least 10 words could be found in the recording on each of the three frequency-based levels, i.e., the 1,001-2,000 frequency range, the 2,001-3,000 frequency range, and the 3,001-5,000 frequency range, of the BNC (Leech et al, 2001). This decision was based on the findings of Matthews (2018) that each of these three levels had unique contributions to L2 listening performance, and on the practice to include 10 items from each 1,000-word-family level for testing vocabulary size (Nation and Beglar, 2007). Each blank was produced by taking away a single word or a two-to-three-word phrase.…”
Section: Instrumentsmentioning
confidence: 99%